Adaptive Resistance to Immunotherapy Directed Against p53 Can be Overcome by Global Expression of Tumor-Antigens in Dendritic Cells - Humar, Matjaz; Azemar, Marc; Maurer, Martina; Groner, Bernd (Frontiers in Oncology, 2014)
Immunotherapy of cancer utilizes dendritic cells (DC) for antigen presentation and the induction of tumor-specific immune responses. However, the therapeutic induction of anti-tumor immunity is limited by tumor escape mechanisms. In this study immortalized dendritic D2SC/1 cells were transduced with a mutated version of the p53 tumor suppressor gene, p53M234I or p53C132F/E164G, which are overexpressed in MethA fibrosarcoma tumor cells. In addition, D2SC/1 cells were fused with MethA tumor cells to generate a vaccine that potentially expresses a large repertoire of tumor antigens. Cellular vaccines were transplanted onto Balb/c mice and MethA tumor growth and anti-tumor immune responses were examined in vaccinated animals. D2SC/1-p53M234I and D2SC/1-p53C132F/E168G cells induced strong therapeutic and protective MethA tumor immunity upon transplantation in Balb/c mice. However, in a fraction of immunized mice MethA tumor growth resumed after an extended latency period. Analysis of these tumors indicated loss of p53 expression. Mice, pre-treated with fusion hybrids generated from D2SC/1 and MethA tumor cells, suppressed MethA tumor growth and averted adaptive immune escape. Polyclonal B-cell responses directed against various MethA tumor proteins could be detected in the sera of D2SC/1-MethA inoculated mice. Athymic nude mice and Balb/c mice depleted of CD4+ or CD8+ T-cells were not protected against MethA tumor cell growth after immunization with D2SC/1-MethA hybrids. Our results highlight a potential drawback of cancer immunotherapy by demonstrating that the induction of a specific anti-tumor response favours the acquisition of tumor phenotypes promoting immune evasion. In contrast, the application of DC/tumor cell fusion hybrids prevents adaptive immune escape by a T-cell dependent mechanism and provides a simple strategy for personalized anti-cancer treatment without the need of selectively priming the host immune system.